Evidence of macroscopic quantum phenomena and conscious reality selection - Larson, Cynthia Sue (Cosmos and history, 2014)
The purpose of this paper is to present an overview of emergent examples of macroscopic quantum phenomena. While quantum theory asserts that such quantum behaviors as superposition, entanglement, and coherence are possible for all objects, assumptions that quantum processes operate exclusively within the quantum realm have contributed to on-going bias toward presumed primacy of classical physics in the macroscopic realm. Non-trivial quantum macroscopic effects are now recognized in the fields of biology, quantum physics, quantum computing, quantum astronomy, and neuroscience, with implications for medicine, psychology and sociology. Robust examples of macroscopic quantum coherence and entanglement contain unmistakable biological advantages, such as are observed in the green sulphur bacteria photosynthesis transfer mechanism, and in the navigational system of the European Robin. Macroscopic quantum processes in the form of an olfactory electron tunneling mechanism best account for the otherwise inexplicable difference observed in the odor of identically-shaped molecules. Evidence of reverse-direction causality is apparent in experiments with large numbers of photons and human subjects. Entanglement, retrocausality, and superposition of states are suggested as causal factors to account for increases in efficacy of the placebo effect. Alternate histories of "flashbulb memories" and embodied cognition are considered as possible examples of superposition of states in a holographic multiverse in which the many worlds of the multiverse and the many worlds of quantum mechanics might just be one and the same thing. KEYWORDS: macroscopic quantum phenomena; quantum biology; retrocausality; placebo effect; embodied cognition; holographic multiverse; alternate histories.